2014
DOI: 10.1016/j.cyto.2013.09.007
|View full text |Cite
|
Sign up to set email alerts
|

Sustained elevation of serum interleukin-18 and its association with hemophagocytic lymphohistiocytosis in XIAP deficiency

Abstract: X-linked lymphoproliferative syndrome (XLP) is a rare primary immunodeficiency characterized by increased vulnerability to Epstein-Barr virus infection. XLP type 1 is caused by mutations in SH2D1A, whereas X-linked inhibitor of apoptosis (XIAP) encoded by XIAP/BIRC4 is mutated in XLP type 2. In XIAP deficiency, hemophagocytic lymphohistiocytosis (HLH) occurs more frequently and recurrence is common. However, the underlying mechanisms remain mostly unknown. We describe the characteristics of the cytokine profil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
89
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(94 citation statements)
references
References 34 publications
4
89
0
1
Order By: Relevance
“…The presence of similar activating mutations in these NLRs, the strong species conservation of the NBD domain, and the role of the NBD in mediating autoinhibition 6 support constitutive NLR oligomerization as an important mechanism in these three diseases. Unlike in CAPS/NOMID patients, the NLRC4 mutation in our patient causes very high circulating and stimulated levels of IL-18, similar to levels seen in other MAS-prone conditions 2628,37 . The factors and molecular mechanisms that differentially regulate NLRC4 versus NLRP3 inflammasome activation are largely unknown and require further study.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…The presence of similar activating mutations in these NLRs, the strong species conservation of the NBD domain, and the role of the NBD in mediating autoinhibition 6 support constitutive NLR oligomerization as an important mechanism in these three diseases. Unlike in CAPS/NOMID patients, the NLRC4 mutation in our patient causes very high circulating and stimulated levels of IL-18, similar to levels seen in other MAS-prone conditions 2628,37 . The factors and molecular mechanisms that differentially regulate NLRC4 versus NLRP3 inflammasome activation are largely unknown and require further study.…”
supporting
confidence: 79%
“…3a). Comparably high levels of serum IL-18 have also been associated with MAS in systemic JIA 25 , AOSD 26 , infection 27 , and XIAP deficiency 28 . Other serum markers that clustered distinctly in NLRC4-MAS included macrophage stimulating cytokines (M-CSF, IL-12p40 29 ), apoptotic factors (TRAIL, LTα), chemokines (CCL7, CXCL12, IL-16), and hematopoietic growth factors (SCF, IL-3) (Fig.3a and Supplementary Fig.…”
mentioning
confidence: 99%
“…More recently, Shimizu et al described the presence of two different cytokine profiles in SJIA with an IL-6 signature in patients with arthritis-related disease manifestations and an IL-18 predominate cytokine profile in patients with MAS (32). In contrast, Wada et al recently demonstrated IL-6, IL-18, tumor necrosis factor (TNF)α, and interferon (IFN)γ elevations in patients with active FHL, Epstein-Barr Virus (EBV)-HLH, and IDAHS (33). In a patient with SLE-related MAS, Shimizu et al demonstrated a more striking TNFα cytokine signature compared to the cytokine profiles from patients with other forms of hyperinflammatory disease (31, 32).…”
Section: Pathogenesismentioning
confidence: 96%
“…Thus, impaired killing of activated macrophages may be a common factor driving macrophage activation in both paradigms. The serum levels of IL-18 associated with XIAP deficiency and NLRC4-MAS are usually in the nanogram-per-milliliter range (the normal range is generally less than 200 pg/mL) and rise during flares (67, 155). Extraordinarily high IL-18 elevation is also seen in some patients with systemic juvenile idiopathic arthritis (sJIA) (156) and Still disease (157) who have had MAS.…”
Section: Autoinflammatory Diseases Caused By Persistent Macrophagementioning
confidence: 99%